Kesan sistem pembelajaran berkomputer matematik berasaskan personaliti - Tang, Howe Eng (2005)
The purpose of this research is to develop a software based on students’ personality type and the skills of creative and critical thinking (KBKK) in learning Linear Motion (GPGL) topic; hence the evaluation of software effectiveness and the exploration pattern of students on MathSoft studied. The research samples consist of initial research sample I, initial research sample II and software evaluation research sample while the research instruments are the test, Myers-Briggs Type Indicator (MBTI), observation, worksheet, interviews, software evaluation forms and digital video recording files. A combination of qualitative and quantitative approaches has been used in analyzing the research data. The finding of software evaluation research shows that after the application of software, the experimental group achieves a significant higher mean mark if compared to that of before the software application. The outcome of the interviews conducted on the experimental group reveals that in overall, these students give positive responses and constructive feedbacks as regards to the effectiveness of software application. The Analysis of Variance (ANOVA) suggests that there is a significant difference in mastering the KBKK for the experimental group. The student categorized under Introvert-Intuitive (IN) shows better learning skill as compared to Introvert-Sensing (IS) and Extravert-Intuitive (EN) in KBKK of sketching and describing velocity-time (v-t) graph. Likewise, IN is also dominant in KBKK of making inference and computing uniform velocity. From the perspective of interaction pattern, EN is matched with the non-linear pattern; IS with linear pattern and Extravert-Sensing (ES) with hierarchy pattern using the MathSoft. IS tends to learn in IS learning mode; IN in IN mode while ES favors the IS mode. The exploration pattern as shown by the majority of the students indicate that they spend a longer time in their own mode of personality. In conclusion, the application of MathSoft in learning GPGL has been accepted positively by the students and expert teachers alike.